2022
DOI: 10.3389/fnut.2022.870923
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ultrasound as Clean Technology for Extraction of Specialized Metabolites From Stinging Nettle (Urtica dioica L.)

Abstract: Nettle is a highly valued medicinal plant that is still largely neglected, both in terms of nutrition and use for pharmacological purposes. Tinctures, i.e., alcoholic extracts, are becoming increasingly popular nettle products, mainly because they allow better availability of phytochemicals and their stability over a longer period of time. The production of alcoholic extracts is a chemically demanding process that is still usually carried out using conventional techniques, which have numerous drawbacks. The us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…using a high-voltage pulse electric field (PEF) and mechanical press [ 14 ]. Ultrasonic-assisted extraction was used for bio substances or phytochemical extraction as a green technology [ 15 ]. Ultrasonic pretreatment was applied for protein extraction from Ascophyllum nodosum using probe-type ultrasound equipment with 750 W capacity and 20 kHz frequency.…”
Section: Introductionmentioning
confidence: 99%
“…using a high-voltage pulse electric field (PEF) and mechanical press [ 14 ]. Ultrasonic-assisted extraction was used for bio substances or phytochemical extraction as a green technology [ 15 ]. Ultrasonic pretreatment was applied for protein extraction from Ascophyllum nodosum using probe-type ultrasound equipment with 750 W capacity and 20 kHz frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several new technologies have been reported for improvement of protein digestion efficiency and production of bioactive compounds including high‐pressure, infrared, microwave, and ultrasound (Switzar et al ., 2013). Among them, ultrasound has been widely used for the extraction of bioactive compounds in many studies (Surin et al ., 2020; Šic Žlabur et al ., 2022) and recently, its positive and promising effects on physicochemical and bioactive properties of food compounds, have greatly increased the interest and attention of food science researchers for more ultrasound applications in the food industry. It has been revealed that the extraction of proteins and bioactive peptides using ultrasound caused an increment in the rate and yield of extraction (Kadam et al ., 2015).…”
Section: Bioactive Propertiesmentioning
confidence: 99%
“…Stinging nettle ( Urtica dioica L.) is a plant species that has been known for its nutritional and medicinal properties since ancient times ( 5 ). Nettle has a great potential in food processing for the production of food supplements, tinctures and capsules ( 6 ) and as a source of green pigments for food colouring ( 7 ). It is also used in the pharmaceutical, cosmetic and textile industries.…”
Section: Introductionmentioning
confidence: 99%
“…It is also used in the pharmaceutical, cosmetic and textile industries. All parts of the plant contain large amounts of different bioactive compounds, but leaves are the richest source, which is why they are intended for consumption as a green leafy vegetable ( 6 ). Nettle leaves contain: carbohydrates, dietary fibre, protein, fatty acids (mostly palmitic and linoleic acids), vitamins (A, B group vitamins, C, D, E and K), minerals (especially P, Ca, Mg and Fe), photosynthetic pigments (chlorophyll a and b, carotenoids), amino acids, organic acids, tannins, terpenoids and phenols ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%